FREQUENCY ANALYSIS AND EVALUATION OF THE IMPLEMENTATION OF CLASS X BIOLOGY PRACTICES IN SENIOR HIGH SCHOOL - Nadia Vermoni Suci; Khairiza lubis; Marlinda Nilan Sari Rangkuti (Universitas Negeri Medan, 2021)
This study aims to determine students' frequency, evaluation, and perceptions on the implementation of practicum in SMA Negeri in Rantauprapat City. The sample in this study were 3 teachers and students of class X MIA at SMA Negeri 1 Rantau Utara, SMA Negeri 2 Rantau Utara and SMA Negeri 1 Rantau Selatan totaling 107 people taken by random sampling. The data analysis technique used is a quantitative descriptive analysis technique, which describes and explains the data based on the field. This research is an explorative survey, namely by observing, interviewing, and exploring. The analysis results show that the average frequency of practicum implementation is 66%, which is quite often done. The laboratory conditions in the three sample schools were classified as very good (83.18%). The student interest in laboratory activities is also classified as very good (86.14%), but some schools, namely SMA Negeri 1 Rantau Utara and SMA Negeri 2 Rantau Utara, experienced problems in the time of practicum implementation (70.44%). The preparation and implementation of the practicum have been carried out very well (88.07%), with 83.90% of reports and evaluations carried out for each practicum activity. However, although it is classified as very good, the average evaluation value is only 59.60, which is quite enough.